Psychometric validation of the Arabic version of the GAD-7 among Lebanese adolescents - Myriam El Khoury-Malhame; Souheil Hallit; Maria-Jose Sanchez-Ruiz; Sleiman El Hajj; Rita Doumit (PLoS ONE, 2025)
Introduction Anxiety is one of the major global mental health concerns, particularly amidst accumulating adversities. It is the leading cause of distress in adolescents worldwide and has a profound deleterious impact on their mental and physical health and wellbeing. This paper seeks to identify and validate the psychometric properties of the Arabic version of the GAD-7 in Lebanon, aiming to improve the much-needed overall mental health screening in Middle Eastern countries. Methods This study includes a cross-sectional design including 638 adolescents in Lebanese public schools. Participants aged 15−18 years were assessed using GAD-7 (anxiety), PCL-5 (post-traumatic stress disorder), and PTGi (post-traumatic growth) in their Arabic versions at two-time points, spaced three months apart. Results Our analyses revealed that the 7 items of the GAD-7 converged into a single factor. Composite reliability of scores was adequate in the total sample (ω = .88/ α = .87). The convergent validity for this model was satisfactory. Results showed invariance across gender at the configural, metric, and scalar levels, with males showing a higher level of wellbeing compared to females. The pre-posttest assessment for the GAD-7 scale was conducted on 359 participants; the intraclass correlation coefficient was adequate 0.83 [95% CI.79;.86]. Our analyses also show that anxiety symptoms were significantly correlated with higher PTSD (r = 0.68; p < .001) and lower PTG (r = −.12; p = .004). Conclusion The Arabic GAD-7 among Lebanese adolescents displayed highly satisfactory psychometric properties, underscoring its validity. This scale could be valuable for educators and clinicians as a screening tool to rapidly detect anxiety among this vulnerable age group as GAD-7 is easy-to-use, easy to understand, culturally sensitive for Arab population and age appropriate for 15–18-year-old students.